2020
DOI: 10.1007/s12325-020-01553-1
|View full text |Cite
|
Sign up to set email alerts
|

Iron Formulations for the Treatment of Iron Deficiency Anemia in Patients with Inflammatory Bowel Disease: A Cost-Effectiveness Analysis in Switzerland

Abstract: Introduction: Iron deficiency anemia (IDA) is a common complication of inflammatory bowel disease (IBD) and can result in reduced quality of life and increased healthcare costs. IDA is treated with iron supplementation, either with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
10
0
2
Order By: Relevance
“…The occurrence of anemia ranges from 9-73% in outpatients and 32-74% upon admission [9,10,13]. The prevalence of iron deficiency in IBD-associated anemia is estimated at around 36-90% [14,15]. According to Woźniak et al, iron deficiency in newly diagnosed IBD patients is as high as 77.53% [6].…”
Section: Idamentioning
confidence: 99%
“…The occurrence of anemia ranges from 9-73% in outpatients and 32-74% upon admission [9,10,13]. The prevalence of iron deficiency in IBD-associated anemia is estimated at around 36-90% [14,15]. According to Woźniak et al, iron deficiency in newly diagnosed IBD patients is as high as 77.53% [6].…”
Section: Idamentioning
confidence: 99%
“…However, IV iron is significantly more costly, being over 60 times more expensive than oral iron [16]. Despite this, cost-effectiveness analysis for the treatment of IDA in IBD patients identified ferric carboxymaltose as the most cost-effective treatment due to suitable adherence to treatment, the high number of patients that respond to the treatment, improvements in hospitalisation rates, and patient quality of life [17].…”
Section: Introductionmentioning
confidence: 99%
“…A CEA of FD vs. FCM in the UK found that haematological response was 9% higher in patients treated with FD than with FCM [24]. On the other hand, two separate analyses of FCM vs. FD and IS in Switzerland and the UK estimated that, in terms of costeffectiveness, FCM was both more effective and less costly for the respective health-care systems [25,26]. In the Nordic context, a 2018 economic evaluation of FD vs. FCM was conducted in the Danish setting, followed by another economic evaluation in 2021, which used data for patients in Norway, Sweden, and Denmark.…”
Section: Introductionmentioning
confidence: 99%